2020
DOI: 10.24093/awej/call6.17
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Saudi students to Blended Learning Environments at the University of Bisha, Saudi Arabia

Abstract: In this study, a survey is conducted to examine learners' perceptions and satisfaction towards blended learning environments designed around the transactional and transformational approaches of learning theories in a blended course in the College of Arts & Sciences, Al-Namas, the University of Bisha, Saudi Arabia. The study aims to evaluate students' perceptions and preferences towards the three components of a blended learning environment: multimedia learning materials, assessment, and interactive activities.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…However, the students in Al-Mubireek's study were only required to participate in online learning for two hours per week. A study by Anas (2020) at Bisha University confirms that Saudi students value blended learning and appreciate the interactivity of online tools, such as discussion forums and collaborative activities.…”
Section: Literature Review Vlles: Merits and Barriersmentioning
confidence: 94%
“…However, the students in Al-Mubireek's study were only required to participate in online learning for two hours per week. A study by Anas (2020) at Bisha University confirms that Saudi students value blended learning and appreciate the interactivity of online tools, such as discussion forums and collaborative activities.…”
Section: Literature Review Vlles: Merits and Barriersmentioning
confidence: 94%
“…However, few EFL studies have explored Blackboard during COVID-19 so far. Notably, the researcher has found few studies focusing on Blackboard in the Saudi EFL context (Anas, 2020;Almekhlafy, 2020;Al-Nofaie, 2020;Hakim, 2020;Khafaga, 2021). In his study, Almekhlafy (2020) found that EFL students in the preparatory year generally did not have positive perceptions toward online learning through Blackboard as the only tool of learning during COVID-19.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, other studies have identified the absence of direct communication as a weakness of online learning (Al-Nofaie, 2020). Anas (2020) confirms that although students appreciate the interactivity of online tools, they value blended learning more. The purpose of this study is to examine the effectiveness of virtual education in reducing language classroom anxiety for Chinese learners in Saudi Arabia and the best way of using virtual educational tools according to students' opinions of their experiences with this mode of education during the quarantine period.…”
Section: Context Of the Studymentioning
confidence: 59%